2016
DOI: 10.1097/md.0000000000005406
|View full text |Cite
|
Sign up to set email alerts
|

The association of serum magnesium and mortality outcomes in heart failure patients

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 39 publications
2
32
0
Order By: Relevance
“…Generally, low levels of plasma magnesium are considered to be one of the risk factors for the development of heart failure 76–78 . Hypomagnesaemia may therefore be an additional risk factor involved in heart failure exacerbation in patients with hypocalcaemic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, low levels of plasma magnesium are considered to be one of the risk factors for the development of heart failure 76–78 . Hypomagnesaemia may therefore be an additional risk factor involved in heart failure exacerbation in patients with hypocalcaemic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in a recent systematic review and meta-analysis of studies conducted in HF patients, hypermagnesemia with serum [Mg 2+ ] ≥1.05 mmol/L was associated with an increased risk of CVD death and all-cause death, but this was not observed for hypomagnesemia [ 74 ]. However, these findings were limited to elderly patients with chronic HF who had reduced left ventricular systolic function.…”
Section: Circulating Magnesium and Cardiovascular Diseasementioning
confidence: 99%
“…An increase in serum magnesium is commonly seen in patients with low GFR (acute or chronic), following treatment with magnesium-containing medications, excessive tissue breakdown (such as sepsis, tumour lysis syndrome and burn) 28 29. An increase in serum magnesium may result in flaccid muscle paralysis, suppressed respiration and apnoea, especially among those with concomitant hypocalcaemia 10 30–33. Altogether, patients who had change in serum magnesium either downward or upward trend carried higher mortality risk compared with those with stable magnesium levels throughout hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal serum magnesium level has been shown to be associated with an increased risk of cardiovascular and all-cause mortality 2 4–10. Studies have demonstrated that dysmagnesaemia is associated with increased left ventricular mass,2 septic shock,3 acute kidney injury (AKI)11 and respiratory failure 12.…”
Section: Introductionmentioning
confidence: 99%